Las publicaciones sobre estudios de cine y medios irlandeses 2021 - Ciara Chambers (Estudios Irlandeses, 2022)
The good news for those of us teaching film and media on university courses is that employers do value the skills developed through academic study. Research skills, critical thinking and an awareness of the historical and contemporary media sphere are to be celebrated it seems. The problem is that students may not realise this until they are well into employment and it is too late to return to campus and engage with their studies more enthusiastically. This was just one of the findings from the illuminating Media Graduates at Work: Irish Narratives on Policy, Education and Industry (Anne O’Brien, Sarah Arnold and Páraic Kerrigan) reviewed by Stephen Boyd. This review joins four others in this year’s section. The hefty Companion to British and Irish Cinema should have been included last year, but due to my oversight, it is featured here instead. Its reviewer, Loretta Goff, notes that it is “a volume that is sure to be heavily engaged with by scholars for years to come” so hopefully its esteemed editor and contributors will forgive its late appearance in these pages!